Trust as a Mediator between Export Commitment and Competitive Advantage on Export SME Performance - Indra, Raharja; Hamdan, Hamdan (Dinasti Publisher, 2024)
Research was carried out to create sustainability of SMEs in the export sector through superior topics in the field of innovation and entrepreneurship with the sub-sector of Micro, Small and Medium Enterprises, abbreviated as UMKM. Important characteristics analytically and experimentally. This research examines the role of Trust as a mediator between Export Commitment and competitive advantage on the performance of Small and Medium Enterprises conducting export businesses in Indonesia. The main phenomenon in this research is the involvement of MSMEs in the supply chain, which is still very minimal, only reaching 6.3 percent in the global value chain in Southeast Asia, far behind Malaysia (46.2%), Thailand (29.6%), the Philippines (20.1%) and Vietnam 21.4%. For national exports, SMEs in Indonesia have only reached 14 percent, far from the government's target of 17 percent. In accordance with the Mercubuana University Research Master Plan for the period 2021 – 2024. The research begins with measuring the Level of Technology Readiness at level 3 with proof-of-concept criteria. Proof of concept, this research has a research objective and developing concepts, especially those related to competitive advantage, commitment and trust, which can improve the performance of Small and Medium Enterprises in the export sector in Indonesia. The research method that uses a quantitative approach with the SEM-PLS data analysis method is considered appropriate. The choice of the SEM- PLS method, because this research is predictive, will of course be able to represent the research model better. This research used 84 respondents from 88 returned questionnaires. The research results of export commitment and trust on the performance of export SMEs have a positive and insignificant effect, competitive advantage on the performance of export SMEs has a significant positive effect.